Common trade policy—EEC's cinderella - Herbert Weichmann (Intereconomics, 1968)
On the occasion of the centenary of the Association of the Grain Merchants of the Hamburg Bourse the First Burgomaster of Hamburg, Professor Weichmann, addressed a meeting on September 19, 1968. The Vice President of the Commission of the European Communities was present when Professor Weichmann spoke of the importance of the grain trade, of the problems of the European agrarian policy and of the fight against world famine. The following is a summary of his address.
Keywords: 330; Agrarian Policy